Investigating Variable Speed Wind Turbine Transient Performance Considering Different Inverter Schemes and SDBR - Okedu, Kenneth E.; Barghash, Hind F. A. (Frontiers in Energy Research, 2021)
In wind energy applications, voltage source converters are employed to achieve energy conservation. Recently, multilevel converters have been showing promising advantages compared to the traditional 2-level converter scheme, due to the fact that they can overcome certain limitations during transient conditions. This paper investigates the transient performance of variable DFIG-based speed wind turbines taking into account different scheme configurations of the power converter system. The schemes investigated are a 2-level six step IGBT inverter, a parallel interleaved 2-level six step IGBT inverter, and a 3-level IGBT inverter. All schemes were compared during severe three-phase to ground fault at the terminal of the DFIG wind turbine using the conventional Phase Lock Loop (PLL) and a DC-chopper protection. A coordinated approach of improving the performance of all the converter schemes with series dynamic braking resistor (SDBR) was analyzed. Investigation of the best location for the SDBR in the DFIG architecture considering the best switching signal was also carried out. Furthermore, a new control strategy of PLL for the DFIG system was proposed in conjunction with the SDBR scheme for the converter systems. Simulations were carried out in Power System Computer Aided Design and Electromagnetic Transient Including DC (PSCAD/EMTDC). The results show that the proposed PLL and SDBR hybrid scheme in the various inverter topologies considered in the study can enhance the performance of the wind generator variables during severe three-phase to ground fault. This is because the proposed hybrid scheme could help to boost the capability of the current and recovery of the wind generator after post-fault scenarios. Also, the voltage source converter leg switched output voltage would be enhanced to maximum change in common mode voltage by the inverter schemes’ modulation of the space vector using the proposed strategy.